Development of a Chemistry Enrichment Book Based on STEAM-Integrated Project based learning for Grade XII Students: Development of a Chemistry Enrichment Book Based on STEAM-Integrated Project based learning for Grade XII Students - Meli Sartika Silaban; Nurfajriani Nurfajriani; Jamalum Purba; Saema Saema (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The development of governance and learning tools from 2022 to 2025 has shown significant improvement, as evidenced by the ministry of education, culture, research, and technology's programs, such as the national book writing school movement and